The contributions of mara institute of technology towards human resource development in Sarawak / Yap Yin … [et al.] - Yap, Yin; Ong, Mooi Lian; Teng, Pek Eng (2000)
According to the Seventh Malaysian Plan, ITM accounts for nearly 17% of the projected output of professional technical manpower during the 1996-2000 period. The main constraints faced by Bumiputeras from Sarawak in furthering their education in Peninsular Malaysia arise from the distanc!l between Peninsular Malaysia and Sarawak, and the heavy financial burden. In addition, due to their rural background, these students could not compete the students from Peninsular Malaysia in gaining entrance to public institutions of higher learning. As such, UiTM Sarawak is important for the Bumiputeras from Sarawak to further their education and also help in meeting the State's manpower needs for its development